(untitled) (Transport systems and technologies, 2018)
In the article described the analysis of the spatial methods, which are based on direct manipulation of pixels in an image. They are used in digital imaging processing and allow to improve the quality of the digital images to facilitate visual analysis. Are considered and modeled such processing methods in the spatial domain, as the gradation conversion (linear and logarithmic transformation), histogram modification (equalization) and image enhancement by using of the Laplace operator. Also presents listings of modeling of these methods in MATLAB. Reflects the results of modeling in the form of images and histograms.